2017
DOI: 10.1186/s13638-017-0926-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance limit of AOA-based localization using MIMO-OFDM channel state information

Abstract: Wireless communication networks are increasingly based on the ubiquitous multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) modulation scheme. Their channel state information is generally obtained each time by a base station receiver as soon as a data packet is successfully received from a mobile device. As it has been shown recently that the MIMO-OFDM channel state information can be used for angle of arrival-based localization, this paper presents a theoretical investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The purpose of data processing is to denoise the original data representing the Y matrix using several common methods for electromagnetic wave denoising to determine whether the results meet the expected conditions. Previous studies [14,15,16,17,18] showed that, among the several traditional methods, wavelet transform has the best filtering effect. Therefore, in this process, wavelet transform was chosen.…”
Section: System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of data processing is to denoise the original data representing the Y matrix using several common methods for electromagnetic wave denoising to determine whether the results meet the expected conditions. Previous studies [14,15,16,17,18] showed that, among the several traditional methods, wavelet transform has the best filtering effect. Therefore, in this process, wavelet transform was chosen.…”
Section: System Designmentioning
confidence: 99%
“…We considered it inappropriate to use traditional filters (e.g., the Butterworth and Chebyshev filters) to remove the high frequency noise contained in CFR because they an not only eliminate noise but also blur the possible rise and fall edges of CFR signals, which are essential for detecting sleep apnea and rollover. Here, we applied the wavelet filter proposed in (Demeechai, Kukieattikool, et al) [18], because it retains the sharp conversion of signals better than other low-pass filters. More specifically, we applied the 8-level b3 wavelet transform to each CFR sequence, and only used detailed coefficients to re-construct.…”
Section: Processing Of C-band Sensingmentioning
confidence: 99%
“…Indoor positioning attracts more and more attention with the increasing requirement of positioning based on services recently [1][2][3]. In general, indoor positioning methods can be classified into three categories according to the parameter used: angle of the signal arrival (AOA) [4], time of the signal arrival (TOA) [5], and the received signal strength (RSS) or the received signal strength index (RSSI) [6]. The distance between the transmitter and receiver can be calculated by multiplying the TOA with the signal travel speed.…”
Section: Introductionmentioning
confidence: 99%
“…Among these parameters, the AOA can be used to estimate the localization of the UEs. There is a study related to AOA-based localization estimation using MIMO-OFDM channel state information (CSI) [9]. In addition, the 3D channel model includes parameters related to polarization and antenna configuration (linear antenna, array antenna) [10].…”
Section: Introductionmentioning
confidence: 99%